logo

Ask Questions, Get Answers

 
X
 Search
Want to ask us a question? Click here
Browse Questions
Ad
Home  >>  CBSE XII  >>  Math  >>  Model Papers
0 votes

Prove that \( tan^{-1}\sqrt x = \frac{1}{2}cos^{-1} \bigg(\frac{1-x}{1+x} \bigg), x \in [0,1].\)

This question is Q.No.9 of Misc. chapter 2
Can you answer this question?
 
 

1 Answer

0 votes
Toolbox:
  • \(\large\frac{1-tan^2\theta}{1+tan^2\theta}\)\(=cos2\theta\)
Given $tan^{-1} \sqrt{x} =\large \frac{1}{2} cos^{-1} \;\; \bigg(\large\frac{1-x}{1+x}\bigg), x\in [0,1]$
We know that \(\large\frac{1-tan^2\theta}{1+tan^2\theta}\)\(=cos2\theta\)
Let $tan \theta = \sqrt x \Rightarrow \theta = tan^{-1}\sqrt x\;$ and $\;x = tan^2 \theta$
Given, $\;x = tan^2 \theta \rightarrow 1 - x = 1 - tan^\theta\;$ and $1 + x = 1 + tan^2\theta$
\(\large \frac{1-x}{1+x}\)\(=\large \frac{1-tan^2\theta}{1+tan^2\theta}\) which as we know is \(=cos2\theta\)
\( \Rightarrow \large\frac{1}{2} cos^{-1}\big(\large\frac{1-x}{1+x}\big)=\large\frac{1}{2}cos^{-1} \bigg( \large\frac{1-tan^2\theta}{1+tan^2\theta} \bigg)\) \( = \large\frac{1}{2}cos^{-1}\: cos2\theta =\large\frac{1}{2}.2\theta= \theta\)
Since \( \theta = tan^{-1}\sqrt x\), L.H.S. = R.H.S.
answered Feb 28, 2013 by thanvigandhi_1
edited Mar 18, 2013 by rvidyagovindarajan_1
 

Related questions

Ask Question
student study plans
x
JEE MAIN, CBSE, NEET Mobile and Tablet App
The ultimate mobile app to help you crack your examinations
Get the Android App
...